The effect of erythropoietin on neonatal hypoxic-ischemic encephalopathy: An updated meta-analysis of randomized control trials - Pan, Jing-Jing; Wu, Yue; Liu, Yun; Cheng, Rui; Chen, Xiao-Qing; Yang, Yang (Frontiers in Pediatrics, 2023)
Objective: Erythropoietin (EPO) seems to have a good application prospect both in experimental models and patients with hypoxic ischaemic encephalopathy (HIE). Data regarding the effect of EPO on death or neurodevelopmental impairment are conflicting. Methods: A search was conducted by two investigators involved in this research in PubMed, Embase, and Cochrane databases for studies in English, in Wanfang, VIP, and Cnki databases for Chinese studies (all last launched on 2022/08/31). Ultimately, we identified 11 original studies, including the EPO group (n=636) and the control group (n=626). Odds ratio (OR) and weighted mean difference were calculated using a random effects or fixed effects model, depending on the data type and heterogeneity of the included studies. Results: 1. The comparison of effectiveness of EPO treatment on HIE: (1) With respect to death, data showed no significant difference between EPO and control groups (OR=0.97, 95% CI, 0.66 - 1.43; P = 0.88); Considering the additional effect of mild hypothermia treatment (MHT), no significant difference was found between EPO+MHT/control+MHT groups either (OR=1.09, 95% CI, 0.69 - 1.73; P = 0.72); With respect to the interference of different routes of medication administration, Meta-analysis further showed no difference between intravenous EPO/control groups (OR=1.13, 95% CI, 0.70 - 1.82; P = 0.62). (2) With respect to cerebral palsy, the analysis showed no significant difference (OR= 0.76, 95%CI, 0.50 - 1.15; P =0.20); Considering the effect of MHT and routes of medication administration, data further showed no difference between EPO group and control group (OR= 1.26, 95% CI, 0.73 - 2.19; P = 0.41). (3) Regarding epilepsy, no significant difference was found (OR= 0.49, 95%CI, 0.20 - 1.19; P= 0.12). MR abnormality was less common in EPO group (OR= 0.39, 95%CI, 0.19 - 0.79; P= 0.008). 2. The comparison of possible adverse events of EPO: EPO treatment would not increase the risk of thrombocytopenia, hypotension, and hepatic and kidney injury. Conclusions: This meta-analysis showed that EPO treatment is not beneficial for reducing death and improving neurological impairment, though it would not increase the risk of adverse events.